Oral manifestations of human papillomavirus infections - Stina Syrjänen (Wiley-Blackwell Publishing, Inc., 2025)
Papillomaviruses are one of the oldest viruses known, dating back 330 million years. During this long evolution, human papillomaviruses (HPV) have developed into hijackers of human cellular and immune systems in which they replicate and remain silent. Systematic studies on oral HPV infections and their outcomes are still scarce. Oral HPV infections have been linked to sexual behaviour, but recent evidence supports their horizontal, mouth‐to‐mouth, transmission. Most HPV infections in infants are acquired vertically from the mother during the intrauterine period, during delivery, or later via saliva. The best‐known benign clinical manifestations of HPV infection are oral papilloma/condyloma and focal epithelial hyperplasia. Evidence is emerging which suggests that some oral HPV infections might persist. Persistent HPV infection is mandatory for HPV‐associated malignant transformation. However, progression of HPV‐induced lesions to malignancy requires additional cofactors. In the early 1980s, we provided the first evidence that a subset of oral cancers and other head and neck cancers might be causally linked to HPV infection. This review summarizes current knowledge on the virus itself, its transmission modes, as well as the full spectrum of oral HPV infections – from asymptomatic infections to benign, potentially malignant oral lesions, and squamous cell carcinoma.